APPLICATION OF DRONES FOR HYDROLOGICAL RESEARCH (Proceedings of the YSU C: Geological and Geographical Sciences, 2023)
The results of using drones to perform hydrometric work are presented, for example: channel reconnaissance, assessment of channel processes, and measurement of flow velocities. The active use of drones in such areas as construction, geological and geodetic surveys suggests the prospects of introducing new equipment into hydrological field work.
Keywords: quadcopter; hydrometry; photo processing